From Evidence to Influence: CGIAR Climate AOW1 Outcomes in 2025 - Edward-Uwadiale, Regina; Miranda, Daniela; Koren, Judith; Mukherji, Aditi (2025)
In 2025, CGIAR’s Climate Action Area of Work 1 had clear objectives including: ensuring that rigorous evidence from food, land, and water systems informs global climate decision-making. Across major science and policy processes, CGIAR scientists contributed directly to how climate risks, adaptation progress, and financing needs are understood and addressed.